Resource Allocation Algorithms For Enhanced Performance In Wireless Virtualization Networks - Saadat, Md. Nazmus; Osman, Husna; Abdullah, Munaisyah; Nassr, Rasheed Mohammad; Dao, Hassan; Zuhiri, Megat F. (International Journal of Engineering and Technology, 2018)
Wireless Virtualization Networks (WVN) is emerging in research community for the spectrum management and efficiency reasons with the shared wireless radio resources like radio frequency (RF) and its infrastructure. The main idea is slicing and sharing it amongst the participating service providers. In this paper, we propose radio resource allocation (RRA) mechanism in settings of WVN to enhance overall network efficiency in next generation networks. The idea considers of course wireless channel quality of the requesting and existing nodes like along with multiple essential and significant factors during decision cycle in response to every allocation request. For simplicity at this stage of research, we categorized user types into higher and lower priority users and implemented our solutions which can be adjusted in later stage. Here, we consider network performance by use of simulation and show that our proposed system outperforms existing works. This would benefit both mobile network operators (MNO) and wireless service providers (WSP) in the WVN environment.